4(x-3)-5x=13

Simple and best practice solution for 4(x-3)-5x=13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x-3)-5x=13 equation:


Simplifying
4(x + -3) + -5x = 13

Reorder the terms:
4(-3 + x) + -5x = 13
(-3 * 4 + x * 4) + -5x = 13
(-12 + 4x) + -5x = 13

Combine like terms: 4x + -5x = -1x
-12 + -1x = 13

Solving
-12 + -1x = 13

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + -1x = 13 + 12

Combine like terms: -12 + 12 = 0
0 + -1x = 13 + 12
-1x = 13 + 12

Combine like terms: 13 + 12 = 25
-1x = 25

Divide each side by '-1'.
x = -25

Simplifying
x = -25

See similar equations:

| -3(w+3)=-9w-21 | | 8x+13y+17z=58 | | 40-5y+8y-y^2= | | -10+4.5=-30 | | 74x-6=19+18x | | 6(5x+6)=306 | | 3[3-(-3)]= | | 8x+7-10x=10+3x+12 | | 8k-k-8= | | 1/3=13/x | | y=25(2x) | | y^2-9y+7y-63= | | 2x+5-7x=7-1(5x+2) | | 0.4x-0.5=0.3x+7 | | ln(x+6)-ln(3)=ln(16) | | (3t+4)t=0 | | -8x-6-x-3= | | y=4x^2-3x-10 | | y^2-5y-6y+30= | | 12=5-x-6x | | x^2-6x+2x-3=9x+27 | | Y=-2(X^4+2X^2)+8 | | 0.66666a+1=11 | | (k+3)+(k+k-11)+k=64 | | 4y=2(y-5)-5 | | 8b=216 | | 3(4x-3)=5-2x/4 | | 6w+9=18w-3w+81 | | -2V+r=2k | | X-12y=-62 | | 0.5=-0.6ln(x)+1 | | y-49=-2 |

Equations solver categories